The Kenya National Human Rights Commission and the promotion, protection and monitoring of socio-economic rights in Kenya - Khayundi, Francis Bulimo Mapati (Rhodes University, Faculty of Law, Law, 2018)
The promulgation of the 2010 Constitution of Kenya introduced socio-economic rights (SERs) amid widespread poverty and rising inequality. This study seeks to answer the overarching question, what role can the Kenya National Commission on Human Rights (KNCHR) play in promoting, protecting and monitoring SERs in Kenya? Further research questions included whether the KNCHR has the requisite powers to perform its mandate and what lessons could be learned from the South African context. The research sought to understand how the local context affects the ability of KNCHR to carry out its mandate. Likewise, it analyses some of the contributions KNCHR has made in the promotion and protection of SERs while identifying the challenges the Commission faces in carrying out its mandate. Several methodologies were utilised to answer the research questions above. The methodologies included the doctrinal method, analysis of secondary sources and interviews with key informants. A comparative legal research methodology was also employed, with the SAHRC being used as a case study on how NHRIs can promote, protect and monitor SERs. The findings from the research argue that the Paris Principles provide the minimum guidelines on the establishment of NHRIs. Compliance with these Principles has not necessarily guaranteed the effectives of NHRIs. Any assessment of an NHRI should be based on its performance and legitimacy considering the local factors obtaining within its jurisdiction. The domestic protection and judicial enforcement of human rights in Kenya, though crucial to the realisation of SERs, has been fraught with challenges. These challenges have meant that the realisation of SERs has been curtailed and necessitated complementary institutions for human rights to be realised. Given the country's constitutional architecture, the KNCHR was one such institution that could complement the role of the judiciary given its wide mandate. With SERs a new feature of the 2010 Constitution, the KNCHR had to find ways to promote SERs in the country considering the local peculiarities such as poverty, a highly political climate and lack of political goodwill from the legislature and executive sometime characterised by open hostility. These challenges and the new nature of these rights called for a comparative study with the SAHRC given some similarities between the two jurisdictions. The SAHRC provided valuable lessons having had more experience in dealing with SERs while navigating similar challenges the KNCHR faced or might face. The findings of the research prompted recommendations directed at the KNCHR and other stakeholders, specifically the legislature and executive on how to address the challenges curtailing the performance of the KNCHR in general and particularly ways in which the Commission could go about in promoting, protecting and monitoring SERs.
Keywords: Kenya Human Rights Commission; Economic rights -- Kenya; Social rights -- Kenya; Kenya -- Economic conditions; Kenya -- Social conditions; Kenya -- Politics and government